2011
DOI: 10.1111/j.1753-0237.2011.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Income and price elasticities and oil‐saving technological changes in ARDL models of demand for oil in G7 and BRIC

Abstract: In recent years, global growth of demand for oil has been mainly due to the increasing demand for energy in major developing nations, namely China, India and Brazil, fuelled by their exceptional economic performance. In the Organization for Economic Cooperation and Development (OECD), on the other hand, and particularly in the G7 countries where more than 70 per cent of OECD demand for oil is consumed, demand for oil has been stagnant and seems to be plateaued. Indeed, per capita consumption for oil in these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…For instance, on the aspect of price substitution an important study by Mazraati and Shelbi (2011) contend that in the context of GHG and ecological issues, there is little to expect that the policy of alternative fuels and alternative fuel vehicles (AFVs) may bring such results, unless sustainable levels of high oil prices are reached. A similar conclusion was reached by Asali (2011) in the analysis of the G-7 and BRIC economies.…”
Section: Oil Price/ Energy Consumption Income and Emissions Nexussupporting
confidence: 79%
“…For instance, on the aspect of price substitution an important study by Mazraati and Shelbi (2011) contend that in the context of GHG and ecological issues, there is little to expect that the policy of alternative fuels and alternative fuel vehicles (AFVs) may bring such results, unless sustainable levels of high oil prices are reached. A similar conclusion was reached by Asali (2011) in the analysis of the G-7 and BRIC economies.…”
Section: Oil Price/ Energy Consumption Income and Emissions Nexussupporting
confidence: 79%
“…Furthermore, oil demand in South and Central America appears to respond more to prices than any other region, with the least response being in North America. While it might be expected that the advanced economies of the OECD should respond more to prices, results from oil demand studies point to a similar outcome as can be found in Dargay and Gately () and Asali ().…”
Section: Data and Estimation Resultssupporting
confidence: 72%
“…There is also a large body of literature which studies asymmetry in areas outside of transportation fuel demand. On the energy demand side, these include demand for petroleum products (Asali 2011, Dargay and Gately 1995, Broadstock et al 2011, residential energy (Haas and Schipper 1998), industrial energy (Adeyemi and Hunt 2007), total energy (Dargay 1992, Adeyemi et al 2010. On the travel demand side, the examples include Gately (1992), Dargay (2001), Greene (2012) and Hymel and Small (2015) for car travel or Wadud (2014Wadud ( , 2015 for air travel; yet Frondel and Vance 2011use household data to find travel demand in Germany was reversible with respect to prices.…”
Section: Review Of the Literaturementioning
confidence: 99%